Analgesic effect of music during laser retinal photocoagulation in diabetics: A randomized, placebo-controlled, crossover trial (Research, Society and Development, 2021)
Objective: To prospectively evaluate the analgesic effect of self-selected music for patients with diabetic retinopathy who underwent laser retinal photocoagulation (LRP). Methodology: This is a controlled, randomized, blinded, two-period crossover clinical trial. Twenty patients (40 eyes) with proliferative diabetic retinopathy who underwent LRP was enrolled. Listening to the patient's favorite music before and during the LRP was the non-pharmacological intervention. The control group (CG) was composed of patients who received only standard pharmacological treatment and the experimental group (EG) of those who received the intervention associated with standard pharmacological treatment. Pain was measured using the Numerical Verbal Scale. Differences in pain scores were tested using Aligned Rank Transformed ANOVA, Mann-Whitney U and Wilcoxon tests. The effect size of the differences was assessed using Rank Bisserial and Partial Square Effect Sizes. Results: Participants were predominantly male (60%), adults (57.4±9.1 years), with comorbidities (65%), with visual impairment ≥ 1 year (65%). Participants who heard music had lower pain scores (EG: 4.80±2.46) compared to those who did not (CG: 6.75±1.59; p=0.013). The application of self-selected music showed a large size of the analgesic effect (η²=0.189). Conclusion: Listening to the patient's favorite music, associated with standard analgesia, is effective in relieving acute LRP-related pain and should be incorporated into clinical practice for the multimodal treatment of pain in this procedure.